Method performance verification and measurement uncertainty evaluation for determination of total active matter content in shampoos - Liljana Anastasova; Rumenka Petkovska; Lidija Petrushevska-Tozi; Zorica Arsova-Serafinovska (Makedonsko Farmacevtski Bilten, 2025)
The aim of our study was to perform in-use method verification of the standard ISO 6842:1989(E) method for determination of total active matter (TAM) content in shampoos. The method was verified for accuracy and precision (method precision, repeatability and intermediate precision). To assure quality, measurement uncertainty was also estimated, through evaluation of the possible sources of uncertainty, using the Nordtest approach. The obtained results for the аccuracy, repeatability (method precision) and intermediate precision confirmed that the standard method could be successfully applied when compared to data for repeatability and intermediate precision provided in ISO 6842:1989(E) method. Measurement uncertainty was estimated for each measurement. The verified method was successfully applied for routine determination of total active matter content in shampoos.